Symptom prevalence differences of depression as measured by BDI and PHQ scales in the Look AHEAD study - Elizabeth M. Vaughan (Obesity Science & Practice, 2020)
Summary Objective To compare depressive symptomatology as assessed by two frequently used measures, the Beck Depression Inventory (BDI‐1A) and Patient Health Questionnaire (PHQ‐9). Methods Investigators conducted a cross‐sectional secondary analysis of data collected as part of the follow‐up observational phase of the Look AHEAD study. Rates of agreement between the BDI‐1A and PHQ‐9 were calculated, and multivariable logistic regression was used to examine the relationship between differing depression category classifications and demographic factors (ie, age, sex, race/ethnicity) or comorbidities (ie, diabetes control, cardiovascular disease). Results A high level of agreement (κ = 0.47, 95% CI (0.43 to 0.50)) was found in the level of depressive symptomatology between the BDI‐1A and PHQ‐9. Differing classifications (minimal, mild, moderate, and severe) occurred in 16.8% of the sample. Higher scores on the somatic subscale of the BDI‐1A were significantly associated with disagreement as were having a history of cardiovascular disease, lower health‐related quality of life, and minority racial/ethnic classification. Conclusions Either the BDI‐1A or PHQ‐9 can be used to assess depressive symptomatology in adults with overweight/obesity and type 2 diabetes. However, further assessment should be considered in those with related somatic symptoms, decreased quality of life, and in racial/ethnic minority populations.